Head in the clouds? Cannabis users' creativity in new venture ideation depends on their entrepreneurial passion and experience - Warnick, Benjamin J.; Kier, Alexander S.; LaFrance, Emily M.; Cuttler, Carrie (Journal of Business Venturing, 2021)
New venture ideation is critical to the entrepreneurial process. To generate creative ideas, some entrepreneurs turn to cannabis, proposing its benefits. However, extant research has not validated such claims. Using a new venture ideation task, we explore differences between cannabis users' and non-users' creativity in new venture ideation by assessing the originality and feasibility of their ideas. We theorized and found that cannabis users generate new venture ideas that are more original, but less feasible, compared to non-users. Further building upon creativity research emphasizing that motivation and knowledge shape creative thinking, we theorize that the cognitive effects of being a cannabis user on idea originality and feasibility are influenced by entrepreneurial passion for inventing—which reflects motivation to explore new venture ideas—and entrepreneurial experience (i.e., founding experience). Consistent with our theorizing, the increased originality and decreased feasibility of cannabis users' ideas surfaced to the extent that they had entrepreneurial passion for inventing and diminished commensurate with their entrepreneurial experience. Our study contributes to the literatures on new venture ideation, entrepreneurial passion, entrepreneurial experience, and cannabis users' creativity by providing an integrated perspective of cognitive, motivational, and experiential factors that drive entrepreneurs' creativity.